Effects of Skin Lightening Cream Agents – Hydroquinone and Kojic Acid, on the Skin of Adult Female Experimental Rats - Owolabi JO; Fabiyi OS; Adelakin LA; Ekwerike MC (Dove Medical Press, 2020)
Joshua Oladele Owolabi,1,2 Oluseyi Sunday Fabiyi,1 Lola Adeola Adelakin,1 Miriammillicent Chinenyenwa Ekwerike1 1Department of Anatomy, Ben Carson School of Medicine, Babcock University, Ilishan-Remo, Nigeria; 2Department of Anatomy, University of Global Health Equity, Butaro, RwandaCorrespondence: Joshua Oladele OwolabiDepartment of Anatomy, Ben Carson School of Medicine, Babcock University Ilishan-Remo, NigeriaTel +2348064884305Email owolabijo@babcock.edu.ngIntroduction: Skin bleaching is the act of using steroid- and chemical-containing products to lighten the skin. Hydroquinone and kojic acid are often used in skin bleaching creams. Hydroquinone was suspected to be harmful. This study investigated the effects of kojic acid and hydroquinone on the skin of adult female Wistar rats and the potential use of aloe vera for amelioration.Materials and Methods: Eighty [n=80] adult female Wistar rats with an average weight of 120 g were randomly divided into eight groups, marked A, B, C, D, E, F, G, and H. Group A animals served as the control group; group B was treated with 2% hydroquinone, group C was treated with 2% kojic acid, group D was treated with 4% hydroquinone, group E was treated with 4% kojic acid, group F was treated with 2% hydroquinone and 2% kojic acid, group G was treated with 4% hydroquinone and 4% kojic acid, and group H was treated with 4% hydroquinone, 4% kojic acid, and aloe vera. The preparations were applied to the tail skin and treatment lasted 28 days. Skin samples were excised and processed using H&E, Masson’s trichrome, and p65 immunohistochemical assays on tissue sections.Results: Hydroquinone caused structural disruptions of the stratum corneum of the epidermis and the overlying keratin. p65 was also prominently expressed in the treated groups. Hydroquinone reduced skin thickness and caused epidermis disruption.Discussion: The prominent expression of p65 in the sections indicated deleterious effects of hydroquinone. Kojic acid was not found to have deleterious effects. Aloe vera prevented extensive disruption of stratum corneum by hydroquinone. The use of hydroquinone in skin lightening creams might raise health concerns. Aloe vera could be protective against hydroquinone.Keywords: hydroquinone, kojic acid, aloe vera, bleaching products, skin